Microprocessor Device of Control System of Grid Multilevel Voltage Inverter with Limitation Transformers Magnetizing Current - Bombyk, V. S. (Visnyk of Vinnytsia Politechnical Institute, 2017)
There has been developed the microprocessor device of the cotrol system of grid multilevel voltage inverter of solar module that allows holding the solar module operation in terms of selection of the maximum power. In the developed device there has been laid the mathematical model of control system of grid-tied multilevel voltage inverter, which considers level of irradiation, temperature of solar module and limitation transformers magnetizing current. The algorithm of the developed microprocessor device has been proposed.